2017
DOI: 10.1016/j.fsigss.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

A GEFI collaborative exercise on DNA/RNA co-analysis and mRNA profiling interpretation

Abstract: A collaborative exercise on DNA/RNA co-analysis and RNA cell typing involving 15 GEFI (Italian working group of ISFG) laboratories was organized in collaboration with the Netherlands Forensic Institute. Participants received: 1) PCR primers for a 19-plex mRNA profiling assay, with reference purified PCR products for each cell type targeted in the multiplex; 2) detailed protocols for DNA/RNA co-extraction, mRNA profiling, and interpretation of results; 3) a set of 8 mock forensic stains (7 single source, one a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The function of CYP2B7P1 and MYOZ1 in vagina remains unknown and their expression in women from different age groups has not been previously investigated. The results obtained confirm that, in general, MYOZ1 is a less sensitive vaginal marker compared to MUC4 and CYP2B7P1, both in R and PM donors [3]. Overall, the three combined vaginal markers included in the 19-plex mRNA profiling assay appear highly efficient in identifying vaginal mucosa irrespective of the donors age category, even in non-recent samples (6-20 months).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The function of CYP2B7P1 and MYOZ1 in vagina remains unknown and their expression in women from different age groups has not been previously investigated. The results obtained confirm that, in general, MYOZ1 is a less sensitive vaginal marker compared to MUC4 and CYP2B7P1, both in R and PM donors [3]. Overall, the three combined vaginal markers included in the 19-plex mRNA profiling assay appear highly efficient in identifying vaginal mucosa irrespective of the donors age category, even in non-recent samples (6-20 months).…”
Section: Discussionsupporting
confidence: 65%
“…Subsets of swabs (n = 13-14), designed as to minimize differences in the ratio between R and PM samples and mean time since swab collection (7.3 months ± 0.4 SD), were distributed to participating laboratories. RNA extraction, cDNA synthesis, mRNA profiling using a 19-plex mRNA assay [1] and scoring of results [2] was done according to protocols previously adopted in a preparatory GeFI collaborative exercise [3]. For capillary electrophoresis, each participant used the available instrumentation (310, 3130, 3500 and SeqStudio genetic analyzers), and the settings (analytical threshold, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Markers, primer sequences, and concentrations were adopted from Van den Berge et al [7]. This molecular system was previously tested in an ISFG Italian Working Group -GEFI collaborative work [8].All thermal cycling steps were accomplished in a Veriti® 96-Well Thermal Cycler (Thermo Scientific®).DNA isolate from the co-extraction process was typed using a conventional STR kit, represented by the AmpFlSTR® NGM PCR Amplification kit (Thermo Scientific®).Detection of all amplified fragments was performed using an ABI PRISM 310 Genetic Analyzer (Thermo Scientific®) and allele calling was accomplished using GeneMapper ID-X V1.0 software (Thermo Scientific®). Allele designation was carried out in comparison to control DNA 007 and allelic ladder provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, gene expression analysis of mRNA markers characteristic of body fluids has been used for the forensic identification of biological samples [ 8 , 9 , 10 , 11 , 12 , 13 ]. Those studies reported bactericidal permeability-increasing protein fold-containing family member A1 (BPIFA1) as a nasal secretion marker [ 14 , 15 ]. BPIFA1 is a lipid-binding protein that plays a role in the innate immune responses of the upper airway [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%